Searching the undetected mtDNA variants in forensic MPS data. (November 2020) - Melchionda, Filomena; Stanciu, Florin; Buscemi, Loredana; Pesaresi, Mauro; Tagliabracci, Adriano; Turchi, Chiara
Highlights: Full mitochondrial genome sequences were generated for 43 Romanian samples by MPS. MPS data were analyzed using the plug-in Variant Caller and the mtDNA-Server tool. We have identified 32 real polymorphisms not detected by both analysis tools used. The full genome data allowed higher haplotypes discrimination and haplogroups resolution. Abstract: The efficiency of MPS in forensic mtDNA analysis has been thoroughly proven, although a reliable and well established data evaluation still remains a critical point. Numerous bioinformatics tools have been developed, but most of them require specific operating systems and high costs, while free open-source programs with user-friendly interfaces are few. In this study, 43 full mtGenomes were sequenced using the Ion Personal Genome Machine™ (PGM™) System and analyzed utilizing the plug-in Variant Caller (TVC) of the Ion Torrent Software Suite and the mtDNA-Server (mDS), a free web-based mitochondrial analysis tool for MPS data. The outcomes of these two different analysis tools were compared to variants noted after manual inspection of the aligned reads performed using Integrative Genomics Viewer (IGV). The comparison highlighted the presence of thirty-nine discordant variant calls, which were resolved by Sanger sequencing that confirmed the presence of all variants, except for 7 deletions. The combined adoption of IGV and Sanger type sequencing confirmatory steps, in addition of TVC and mDS analysis, resulted in a more accurate variants assignment with the detection of 32 additional true polymorphisms, which were noted in the final dataset. Regarding the heteroplasmy issue, out of a total of thirty heteroplasmic variants, twenty-eight were detected by the TVC, while the mDS detected twenty-two. Overall, none of the used bioinformatics tools were the perfect choice and a secondary analysis with an expert's opinion in complete mtGenome MPS data evaluation is still required in forensic genetic analysis.